Exploring the putative role of kallikrein‐6, calpain‐1 and cathepsin‐D in the proteolytic degradation of α‐synuclein in multiple system atrophy. (29th August 2018) - Kiely, A. P.; Miners, J. S.; Courtney, R.; Strand, C.; Love, S.; Holton, J. L.
Abstract : Aims: There is evidence that accumulation of α‐synuclein (α‐syn) in Parkinson's disease (PD) and dementia with Lewy bodies (DLB) results from impaired removal of α‐syn rather than its overproduction. Kallikrein‐6 (KLK6), calpain‐1 (CAPN1) and cathepsin‐D (CTSD) are among a small number of proteases that cleave α‐syn and are dysregulated in PD and DLB. Our aim in this study was to determine whether protease activity is altered in another α‐synucleinopathy, multiple system atrophy (MSA), and might thereby modulate the regional distribution of α‐syn accumulation. Methods: mRNA and protein level and/or activity of KLK6, CAPN1 and CTSD were measured and assessed in relation to α‐syn load in multiple brain regions (posterior frontal cortex, caudate nucleus, putamen, occipital cortex, pontine base and cerebellar white matter), in MSA ( n  = 20) and age‐matched postmortem control tissue ( n  = 20). Results: CTSD activity was elevated in MSA in the pontine base and cerebellar white matter. KLK6 and CAPN1 levels were elevated in MSA in the putamen and cerebellar white matter. However, the activity or level of these proteolytic enzymes did not correlate with the regional distribution of α‐syn. Conclusions: Accumulation of α‐syn in MSA is not due to reduced activity of the proteases we have studied. We suggest that their upregulation is likely to be a compensatory response to increased α‐syn in MSA.